Posttraumatic Pneumocephalus: The Spectrum in a Tertiary Neurosurgery Center - Kumar, Vinod; Nair, Rajesh Parameshwaran; Hegde, Ajay; R., Girish Menon (Indian Journal of Neurotrauma, 2017)
Traumatic head injuries are often encountered in the emergency triage, and usually these patients have open head injuries or traumatic pneumocephalus secondary to base of skull fractures. The first line of management involves conservative approaches that include the use of carbonic anhydrase inhibitors, loop diuretics, and, occasionally, lumbar CSF diversion techniques. Surgical intervention is considered once conservative management fails after 2 weeks of institution of conservative management. Here, we discuss the various clinical scenarios, clinical presentation, treatment dilemmas, and possible complications in patients with traumatic pneumocephalus.
Keywords: pneumocephalus; air bubble; pneumoventricle; Mount Fuji sign